Edukasi Pencegahan dan Cara Pengendalian Diabetes Melitus Melalui Poster Digital di Media Sosial untuk Meningkatkan Kesadaran Masyarakat - Ananda Ninuk Rezkylia; Anisa Hul Jannah; Arum Shochichah; Citra Lestari; Dassya Mukni Butuni; Aliya Aliya; Devi Savitri Effendy; Ramadhan Tosepu; Febriana Muchtar; Hariati Lestari; Siti Nurfadilah H.; Nurmaladewi Nurmaladewi; Nurhijrianti Akib (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
Diabetes mellitus is a non-communicable disease with a continuously increasing prevalence worldwide and in Indonesia. Limited public knowledge regarding its risk factors and prevention contributes to a higher incidence of the disease and its complications. This community engagement activity aimed to improve public awareness and knowledge of diabetes mellitus prevention and management through a digital poster campaign on social media. The program involved situation analysis using secondary data, poster development, validation by content and media experts, publication on Instagram, and evaluation of audience responses. Three digital posters were created, focusing on healthy eating habits, reducing excessive sugar intake, and promoting physical activity and weight management. Content validation resulted in an average feasibility score of 76% (feasible), while media validation achieved 83.3% (highly feasible). The campaign demonstrated strong public engagement, with Poster 3 reaching 1,416 accounts and generating the highest number of interactions (139), whereas Poster 1 recorded the highest engagement rate (30.33%). Overall media acceptance reached 86.3%, categorized as very good, indicating that the digital posters are effective and well accepted as health education media to enhance public awareness and support diabetes mellitus prevention and management.